2010
DOI: 10.1007/s11999-009-0964-x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Treatment of Less Severe Intraarticular Calcaneal Fractures

Abstract: Percutaneous treatment of calcaneal fractures is intended to reduce soft tissue complications and postoperative stiffness of the subtalar joint. We assessed the complications, clinical hindfoot alignment, motion, functional outcome scores, and radiographic correction of percutaneous arthroscopically assisted reduction and screw fixation of selected, less severe fractures. We performed percutaneous reduction and screw fixation in 61 patients with Type II (Sanders et al.) calcaneal fractures. In 33 of 61 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
142
5
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(154 citation statements)
references
References 39 publications
0
142
5
7
Order By: Relevance
“…Tornetta [18] reported using the EssexLopresti reduction technique for treating Sanders IIC fractures with screw fixation. There have been numerous reports of less invasive surgical techniques using screws [6,8,9], bioabsorbable screws [20], arthroscopically assisted with screws [10], K wires [7,12], external fixation to aid reduction with percutaneous screws [11], and external fixation [21] alone to treat displaced intra and extraarticular fractures with satisfactory results described. Schildhauer and Sangeorzan [22] described the use of a push screw, which allows controlled and gradual reconstitution of the length and height (Böhler's angle) of the hindfoot, though, it is only recommended as a temporary salvage procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tornetta [18] reported using the EssexLopresti reduction technique for treating Sanders IIC fractures with screw fixation. There have been numerous reports of less invasive surgical techniques using screws [6,8,9], bioabsorbable screws [20], arthroscopically assisted with screws [10], K wires [7,12], external fixation to aid reduction with percutaneous screws [11], and external fixation [21] alone to treat displaced intra and extraarticular fractures with satisfactory results described. Schildhauer and Sangeorzan [22] described the use of a push screw, which allows controlled and gradual reconstitution of the length and height (Böhler's angle) of the hindfoot, though, it is only recommended as a temporary salvage procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported satisfactory reductions of both intra and extra-articular fractures and reduced wound complications using MIRF [6][7][8][9][10][11][12][13][14]. In addition, it is advantageous to improve hindfoot morphology in an 'at risk' group of patients who otherwise would potentially be treated nonoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…After the reduction, the fragments are rigidly fixed together using a metallic plate and screws, or intramedullary nails [2]. Although this open procedure can be effective, it is associated with extensive damage to the soft tissues, slow bone healing and increased risk of infection, with consequent prolonged hospitalization, rehabilitation time, and healthrelated costs [3]. Minimally invasive surgical techniques (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The 2D nature of these images (Fig.1d), the localized and limited 2D-field of view, and their low resolution, do not provide enough information to the surgeon with respect to the fracture alignment and rotation, which is essentially a threedimensional problem. Also, the high forces occurring during the reduction process increase the physical load on the surgeon preventing the reduction movements [5] and occasionally resulting in suboptimal fracture reduction [3].…”
Section: Introductionmentioning
confidence: 99%
“…Congenital and acquired abnormalities of the foot and ankle are often associated with a varus or valgus misalignment of the hindfoot [1][2][3]. Hindfoot alignment is first estimated clinically during the physical examination, and is subsequently quantified on radiographs as a basis for treatment decisions, preoperative planning, and monitoring of the postoperative course [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%